2002
DOI: 10.1159/000046990
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Hemodialysis Catheter-Related Bloodstream Infection Using an Antimicrobial Lock

Abstract: Among currently available vascular access options for hemodialysis, central venous catheters show the poorest reliability, with frequent complications of thrombosis and stenosis impairing patency. The most serious problem, however, is catheter-related bloodstream infection (CRBI), which is typically a cause for removal of the catheter and protracted systemic antibiotic therapy. In our experience, a totally implanted device (Dialock®, Biolink Corp.) seems to confer a better global protection against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 11 publications
0
12
0
3
Order By: Relevance
“…Studies have found that taurolidine works by reducing the biofilm formation . A subgroup of the CVCs included in this study was also examined by scanning electron microscopy and no difference was found in the biofilm development between the two groups .…”
Section: Discussionmentioning
confidence: 93%
“…Studies have found that taurolidine works by reducing the biofilm formation . A subgroup of the CVCs included in this study was also examined by scanning electron microscopy and no difference was found in the biofilm development between the two groups .…”
Section: Discussionmentioning
confidence: 93%
“…Our search yielded 63 published reports (figure 1); 56 studies were excluded because they evaluated lock solutions other than vancomycin [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], did not have a control group [47][48][49][50], used a lock solution for treatment rather than prevention [45,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65], did not use a randomized, controlled study design [66][67][68][69], assessed the utility of a lock solution for prevention of BSI with only 1 type of organism [70], were reviews [19,20,56,[71][72][73][74][75]...…”
Section: Resultsmentioning
confidence: 99%
“…Taurolidine is a broad-spectrum antimicrobial agent that has been reported to reduce bacteremia rates in patients with hemodialysis, nutrition and pediatric catheters (11)(12)(13). It acts by a direct effect on bacterial cell walls and has never been associated with resistance (12,(14)(15)(16).…”
mentioning
confidence: 99%